NT-proBNP and diastolic left ventricular function in patients with Marfan syndrome - Gehle, Petra (Int J Cardiol Heart Vasc, 2016)
AIMS: Subclinical diastolic dysfuntion in patients with preclinical heart failure with preserved ejection fraction (HFpEF) has been demonstrated in patients with Marfan syndrome (MFS). We investigated the relationship between diastolic dysfunction and NT-proBNP levels in patients with MFS. METHODS AND RESULTS: NT-proBNP, C-reactive protein (CRP) and diastolic function were assessed in 217 patients with MFS (31 ± 16 y, 110 f. and in 339 patients referred for suspected MFS in whom the diagnosis was ruled out according to the Ghent nosology (30 ± 15 y, 154 f). Assessment of cardiovascular remodeling, diastolic function in echocardiography, and NT-proBNP was analyzed with univariate analysis and multi-parameter analysis of covariance (MANCOVA). NT-proBNP was 70.6 ± 74.8 pg/ml in patients with Marfan syndrome and 58.4 ± 100.3 pg/ml in controls (p = 0.002, Kolmogorov–Smirnov). There were significant intergroup differences regarding end-diastolic left ventricular volume (p < 0.001), and aortic diameter (p < 0.001). The ratio of early diastolic mitral flow velocity (E) to early relaxation velocity in tissue Doppler (e′), E/e′ (p < 0.001) was significantly higher in patients with Marfan syndrome than in controls, whereas e′ (p < 0.001) and the ratio of E to inflow velocity during atrial contraction (A), E/A (p = 0.012) was significantly lower. Besides age and gender, diagnosis of MFS, diastolic function (e′ and E/e′), Z-Score of aortic diameter, and left ventricular size were identified as significant independent parameters with impact on NT-proBNP levels. CONCLUSIONS: MFS patients presenting with normal ejection fraction show disturbed diastolic function and higher NT-proBNP levels, which is partly explained by aortic Z-score. Assessment of diastolic function and NT-proBNP levels may therefore detect early abnormalities and guide surveillance and prevention management of patients with MFS.